MycoNews 2023: Editorial, news, reports, awards, personalia, and book news - David L. Hawksworth (IMA Fungus)
Abstract This fifth annual edition of MycoNews starts with an editorial on the critical importance of International Mycological Congresses (IMCs) to the health of mycology. Items on Counting down to IMC12, the State of the World’s Plants and Fungi 2023, and progress towards Improving nomenclatural stability in medically important fungi follow. Reports are provided of several mycological meetings in 2023: the Asian Mycological Congress, XIX Congress of European Mycologists, a meeting of European Mycological Groups and Societies, the XI Latin American Mycological Congress, Westerdijk Spring Symposium on Fungal Evolution, the Brazilian Society of Mycology, the Annual Meeting of the Mycological Society of China, and the Fifth Iranian Mycological Congress. Information is provided on how to make nominations for the various IMA Awards due to be presented at IMC12 in August, the new Future is Fungi Award launched in 2023, and the Adel-Azeem and Stamets Award for work on Psilocybe in Africa. The Westerdijk Fungal Biodiversity Institute Awards for 2023 were made to Andrey Yurkov and Cathie Aime and the citations to those awards are provided. We include tributes to the passing of two eminent mycologists, Lorelei Norvell and Takashi Matsushima, and also send birthday greetings to Bryce Kendrick who turned 90, and Maria Ławrynowicz, Yu Li, and Anthony Whalley who all became octogenarians. Reviews of seven mycological books published in 2022–2023 are included in the Book News section.